(3CMGOjK hMcGjGJ hEfTGOGJs - (3YHO Gddg Hf eMeO GdfhbGfjs ((3OeTb s)
(3ChdgG (B:s
(3bGd SeYJ YeQ Hf GdNWGH jbhd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd EfeG GdCYeGd HGdfjg hEfeG dCeQF eG fhi aef cGfJ gLQJg Edi Gddg hEdi QShdg agLQJg Edi Gddg hEdi QShdg hef cGfJ gLQJg Edi OfjG jUjHgG Ch CeQCI jJRhLgG agLQJg Edi eG gGLQ Edjg s
(3BNQgG (B:s
(3aEPG CHUQJg CHUQJfi hEPG CHUQJfi CHUQJfG BNQ GdLRA hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3HBNQgG bQGAGJ hSeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3JhfS (B(4520) s
Keywords: (3GdMOjK h GdeUWdMs